Recall as a didactic strategy to strengthen the learning of Calculus in Engineering - Oyarzún Fölsch, Waldo Patricio; Mieres Sepúlveda, Guillermo (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
To evaluate the impact of a didactic strategy based on the ability to evoke in order to strengthen the learning of Calculus among Engineering students at Universidad San Sebastián. Methods: A mixed-methods design with a sociocritical approach was developed, incorporating guided evocation-based activities, formative assessment, interviews, and surveys. The sample consisted of 60 students distributed between a control group and an experimental group. The intervention involved evocation activities through spaced retrieval, contextualization of problems, and transfer to new situations. Results: The experimental group showed significant improvements in performance, increased explanatory capacity, greater cognitive autonomy, and a more stable understanding of the concepts involved in changing the order of integration in general regions of double integrals in Cartesian coordinates. Conclusions: The ability to evoke enhances Calculus learning by activating priorknowledge and transferring it to new, contextualized, and challenging problems. The proposal aligns with dialectical philosophical foundations that emphasize practice as the instance through which knowledge is transformed, and with educational models centered on “Feeling, Knowing, and Doing” for professional development.
Keywords: Evocation; Calculus; Meaningful Learning